Relatório de estágio curricular obrigatório: área de clínica médica de pequenos animais - Romitti, Nicole Schiavenin (My University, 2025)
The mandatory curricular internship was completed at the Veterinary Hospital Institute of the University of Caxias do Sul (IHVET-UCS), in the Small Animal Internal Medicine service, from July 28 to October 31, 2025, totaling 411 hours. It was carried out under the guidance of Prof. Dr. Eduardo Conceição de Oliveira and supervised by Prof. Manoela Maria Bianchi, M.Sc. The report describes the hospital's structure, its technical team, the caseload attended, and the activities performed during the internship, and it also presents two observed clinical cases. A total of 74 consultations were monitored, with tegumentary (skin) disorders being the most frequent, followed by genitourinary diseases. Of the cases, 54 (72.97%) were dogs and 20 (27.03%) were cats, with mixed-breed male dogs being the most commonly treated. A total of 829 diagnostic and therapeutic procedures were performed or observed, the most recurrent being venipuncture to obtain vascular access and the administration of medications. Among the conditions observed, external otitis was the most common in dogs, while suture dehiscence and skin lacerations predominated in cats. Of the clinical cases followed, one involved a high-grade cutaneous mast cell tumor on the right pelvic limb of a mixed-breed dog, which was treated surgically by amputation; adjuvant therapy was indicated but it could not be performed. The second case involved a rescued mixed-breed female cat diagnosed with fetal maceration, requiring clinical management and assessment of associated systemic complications. This internship represented an essential stage in the professional development, allowing the application of theoretical knowledge in practice and fostering a better understanding of the challenges and responsibilities of the veterinary profession. [resumo fornecido pelo autor]
O estágio curricular obrigatório foi realizado no Instituto Hospitalar Veterinário da Universidade de Caxias do Sul (IHVET-UCS), na área de Clínica Médica de Pequenos Animais, entre 28 de julho e 31 de outubro de 2025, totalizando 411 horas, sob orientação do Prof. Dr. Eduardo Conceição de Oliveira e supervisão da Profa. Ma. Manoela Maria Bianchi. O relatório apresenta a estrutura do hospital veterinário, sua equipe técnica, a casuística acompanhada e as atividades desenvolvidas ao longo do período, além de relatar dois casos clínicos observados. No total, foram acompanhadas 74 consultas, sendo as afecções do sistema tegumentar as mais frequentes, seguidas pelas doenças geniturinárias. Dentre os atendimentos, 54 (72,97%) foram em cães e 20 (27,03%) em gatos, sendo os cães machos sem raça definida (SRD) os mais atendidos. Foram realizados ou acompanhados 829 procedimentos diagnósticos e terapêuticos, destacando-se entre os mais recorrentes, a punção venosa para obtenção de acesso e a administração de medicações. Entre as afecções observadas, a otite externa foi a mais comum em cães, enquanto, nos gatos, predominaram casos de deiscência de sutura e lacerações cutâneas. Entre os casos clínicos acompanhados, destacou-se um mastocitoma cutâneo de alto grau em membro pélvico direito de um canino SRD, tratado cirurgicamente por amputação, sendo indicada terapia adjuvante, que não pôde ser realizada. O segundo caso referiu-se a uma felina SRD, resgatada em condição de rua, que apresentou maceração fetal, exigindo manejo clínico e avaliação das complicações sistêmicas associadas. Essa experiência representou uma etapa essencial para o aprimoramento profissional, permitindo aplicar os conhecimentos teóricos na prática e compreender os desafios e responsabilidades do médico-veterinário. [resumo fornecido pelo autor]
Keywords: Medicina veterinária; Hospitais veterinários; Clínica médica; Cirurgia veterinária; Animais - Doenças - Tratamento